Indian Nurse's Diaspora in Global Health Care; Uncovering the Key Findings About Migration of Nurses from Indian Perspective: A Review - Khina Sharma; Ashok Kumar; Mahendra Kumar; Ranjit Pal SIngh Bhogal (Medsci Publications, 2022)
There is no doubt that consequences of health workforce migration are serious for any developing country. The world's largest health care migrating population is from India. India has a population of 1.38 billion, about 17.7% of the world's population and we, as a nation, are struggling to prepare future-ready health care professionals and our own health professionals' needs are not met. However, large numbers of Indian nurses migrate to developed countries due to numerous factors. Economic factors are considered main force for migration, but not always purely responsible, as nurses look for safety, security, respect, and dignity of their profession. This scoping review is employed to find causes, consequences, and strategies related to international migration of Indian Nurses.